An exploratory study of TV home shopping in Singapore. - Ho, Huoy Jiun. (2013)
The extension of local television broadcast to 24 hours a day, 7 days a week has created the opportunity for marketers to reach out to consumers directly. Marketing through television is often termed more formally as direct response television, or DRTV for short. A much faster pace of life and therefore greater need for convenience has had a direct stimulus on the growth of marketing through television here. Coupled with the sustained saturation in the store-based retail scene in Singapore, marketers will be looking out for alternative and more direct ways to market to their customers. DRTV are showing signs that it is here to stay, for good.